2014
DOI: 10.1002/eco.1542
|View full text |Cite
|
Sign up to set email alerts
|

Effects of woody vegetation on shallow soil moisture at a semiarid montane catchment

Abstract: iii ACKNOWLEDGEMENTS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 85 publications
2
8
0
Order By: Relevance
“…Vegetation (fPAR and actual evapotranspiration) was also important in explaining BFI variability in all regions. Similar insights have been made with regard to the forest growth stage and BFI, (Lacey & Grayson, 1998) and soil moisture reduction has also been related to woody vegetation (Traff, Niemann, Middlekauff, & Lehman, 2015).…”
Section: Variability In Climate and Vegetation Effects On Streamflosupporting
confidence: 69%
“…Vegetation (fPAR and actual evapotranspiration) was also important in explaining BFI variability in all regions. Similar insights have been made with regard to the forest growth stage and BFI, (Lacey & Grayson, 1998) and soil moisture reduction has also been related to woody vegetation (Traff, Niemann, Middlekauff, & Lehman, 2015).…”
Section: Variability In Climate and Vegetation Effects On Streamflosupporting
confidence: 69%
“…The Cache la Poudre catchment is located near Rustic, Colorado and is in the Southern Rockies ecoregion (Omernik, 1987;Traff, 2013). The catchment area is approximately 8.0 ha, and the climate is semi-arid with 415 mm mean annual precipitation (Lehman and Niemann, 2008).…”
Section: Cache La Poudrementioning
confidence: 99%
“…The calibrated parameters suggest that interception and root water uptake reduce the soil moisture more than shading increases it. This behavior might be unrealistic because previous studies in semiarid watersheds have shown that vegetation cover is associated with greater soil moisture at shallow depths [ D'Odorico et al ., ; Traff et al ., ]. Furthermore, this type of vegetation dependence predicts very dry conditions for the irrigated agricultural fields, which is also unlikely.…”
Section: Resultsmentioning
confidence: 99%
“…Another class of downscaling methods use topographic and vegetation data because these variables have been shown to be related to fine scale soil moisture variations [Western et al, 1999;Gomez-Plaza et al, 2001;Brocca et al, 2007;Traff et al, 2015]. These downscaling methods often reach 10-30 m resolutions, but they typically have been applied to small catchments with low topographic relief.…”
mentioning
confidence: 99%